Studies on the Removal of Cadmium Toxic Metal Ions by Natural Clays from Aqueous Solution by Adsorption Process - Rajaa Bassam; Achraf El hallaoui; Marouane El Alouani; Maissara Jabrane; El Hassan El Khattabi; Malika Tridane; Said Belaaouad (Journal of Chemistry)
The aim of this study is the valorization of the Moroccan clays (QC-MC and QC-MT) from the Middle Atlas region as adsorbents for the treatment of water contaminated by cadmium Cd (II) ions. The physicochemical properties of natural clays are characterized by ICP-MS, XRD, FTIR, and SEM techniques. The adsorption process is investigated as a function of adsorbent mass, solution pH, contact time, temperature, and initial Cd (II) ion concentration. The kinetic investigation shows that the adsorption equilibrium of Cd (II) ions by both natural clays is reached after 30 min for QC-MT and 45 min for QC-MC and fits well to a pseudo-second-order kinetic model. The isotherm study is best fitted by a Freundlich model, with the maximum adsorption capacity determined by the linear form of the Freundlich isotherm being 4.23 mg/g for QC-MC and 5.85 mg/g for QC-MT at 25°C. The cadmium adsorption process was thermodynamically spontaneous and exothermic. The regeneration process showed that these natural clays had excellent recycling capacity. Characterization of the Moroccan natural clays before and after the adsorption process through FTIR, SEM, XRD, and EDX techniques confirmed the Cd (II) ion adsorption on the surfaces of both natural clay adsorbents. Overall, the high adsorption capacity of both natural clays for Cd (II) ions removal compared to other adsorbents motioned in the literature indicated that these two natural adsorbents are excellent candidates for heavy metal removal from aqueous environments.